Economic development,institutions,and technique change: Intensification of cattle-feeding techniques by the Giriama of Kenya's coast province. - Swallow, K.A. (University of Wisconsin-Madison, 1996)
In order to strengthen economic development policy, a broad definition of economic development is offered: the mutually reinforcing increase in collective institution-building and individual ends-meeting capacities. A conceptual framework based on this definition is presented that unites into a cohesive whole concepts from literature on economic development, technique change, and collective action. The framework is focused on the institution-building capacity of a group of resource users and the ends-meeting capacities of the group's members. The elements of the framework are: extra-local factors such as national policy; physical-technical factors; the characteristics of the broader local social system; the characteristics of the resource-user group; the group's institutional regime; and short-term patterns of interaction and production. To flesh out linkages between elements of the conceptual framework, a case study . was done of the Giriama of Kenya's Coast Province. Emphasis was placed on one Giriama village located in the coconut-cassava agro-ecological zone. An historical analysis of the economic development of the Giriama was done using secondary literature. Field work focused on understanding short-term patterns of interaction and production behavior with respect to cattle-feeding techniques. Quantitative data was provided by single-visit questionnaire interviews and longitudinal monitoring. Analysis focused on the factors that affected use of a variety of means of access to others' land and feeds. Customarily, interactions over access to fellow villagers' fallowed land and crop residues for cattle grazing took place in the public-action sector. Intensification ofland use and the emergence of commercial-dairying meant that land owners placed increasing value on their fallow growth and residues such that they began to look for ways of realizing, if only gradually, the exclusive rights implied by the title deeds that they held. Indeed, it was found that the majority of interactions over access to others' land or feeds were not conducted through the public-action sector. Rather they were conducted through bargaining transactions that represented the grey area between the three collectively-defined action sectors: private, public, and collective. One factor that affected the adoption of commercial dairying was the greater tendency for interactions over feeds for these enterprises to be conducted in the collective- or private-action sectors, or the grey area between them. The factors that affected the capacity of the village to choose and implement institutions to define action sectors for transactions over land and feeds were analyzed, and implications for policy were examined